Empat Belas Tahun Perkembangan Peraturan Keamanan Hayati dan Keamanan Pangan Produk Rekayasa Genetik dan Implementasinya di Indonesia - Muhammad Herman (Jurnal AgroBiogen, 2010)
Fourteen Years of Development of Biosafety and FoodSafety Regulations of Genetically Engineered Productsand their Implementation in Indonesia. M. Herman. InIndonesia, the need for biosafety and food safety regulationof genetically engineered products (GEP) is well recognized.The Food Law and the Decree on Provisions of Biosafety ofGenetically Engineered Agricultural Biotechnology Productshas been signed respectively by the President of Republic ofIndonesia in 1996 and by the Minister of Agriculture in 1997.The biosafety and food safety regulation of GEP comprise ofguidelines, ministerial decree, joint ministerial degree,government regulation, presidential regulation, presidensialdecree, and law. In the implementation of biosafety regulationduring the year of 1999-2001, there were five GE cropsand two enzymes products derived from GE microorganismsfor feed additive have been decraled as safe to the environment.One of the five GE crop declared for environmentsafety, the insect resistant (IR) cotton (Bt cotton) was commercializedfor limited released in seven districts of SouthSulawesi during 2001-2003. Whereas, from 2001-2010 thereare 13 GE crops have been studied in the greenhouse ofbiosafety containment and confined field trials, among ofthose there are two GE crops, herbicide tolerant (HT) GEmaize and drought tolerant (DT) GE sugarcane have beenassessed and recommended for environment safety. Fiveapplication of animal vaccine derived from GE microorganismsfor studied in the biosafety containment andconfined field have been submitted to the regulator. Inaddition to biosafety regulation, food safety regulation hasalso been implemented after the Food Safety AssessmentGuideline for GEP has been signed by the Head of Food andDrug Inspection Agency in July 2008. Food safety assessmenthas been conducted on 10 GE crops such as HT maize, HTsoybean, IR maize, amylase modification maize and DTsugarcane. There are some constraints encountered duringthe implementation of biosafety and food safety regulation.The constraints are the lack of commitment of relatedinstitution involved in the regulation, lack of understading onthe regulation, and difficulties of implementing the regulationon the import products such as maize and soybean forfood and feed process.